1994
DOI: 10.1111/j.1469-8749.1994.tb11853.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Blindness and Severe Visual Impairment in Children in Chile

Abstract: SUMMARY Three hundred and eighteen of 421 children (76 per cent) registered in Chile's 10 schools for the blind were examined. 84 per cent of these had severe visual loss (severe visual impairment or blindness), which was attributable to hereditary factors in 29‐6 per cent, intra‐uterine factors in 8‐2 per cent, perinatal factors in 22‐5 per cent and childhood factors in 11‐2 per cent. The aetiology could not be determined in 28‐5 per cent. Retinopathy of prematurity (ROP) accounted for 17‐6 per cent of all ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 9 publications
0
61
0
3
Order By: Relevance
“…6 This discrepancy may be explained by the higher frequency of corneal injuries secondary to vitamin A deficiency and infections in African and Asian countries, where they account for up to 50% of the cases of blindness, and in Bolivia, the Dominican Republic, and Peru, where they account for 20%. 15,16 In the present study, the major cause of visual impairment was congenital glaucoma, due to the referral of patients to the Congenital Glaucoma Service of the Ophthalmologic Clinic. International data indicate that congenital glaucoma accounts for 6% of the cases of blindness in childhood worldwide.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…6 This discrepancy may be explained by the higher frequency of corneal injuries secondary to vitamin A deficiency and infections in African and Asian countries, where they account for up to 50% of the cases of blindness, and in Bolivia, the Dominican Republic, and Peru, where they account for 20%. 15,16 In the present study, the major cause of visual impairment was congenital glaucoma, due to the referral of patients to the Congenital Glaucoma Service of the Ophthalmologic Clinic. International data indicate that congenital glaucoma accounts for 6% of the cases of blindness in childhood worldwide.…”
Section: Discussionmentioning
confidence: 65%
“…In developing countries, available data on visual impairment, 4,5,15,16 are scarce, and do not reflect the magnitude of the problem of childhood visual impairment. 4,5 Studies conducted at visual impairment assistance services may contribute to the knowledge on the local characteristics and help with planning actions, although they represent only the part of the population that had access to care,.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports from West Africa, South India, and Chile showed that lens abnormalities accounted for 15.5%, 7.4%, and 9.2% of blindness in such schools. 5 Similar studies conducted in Malawi, Kenya and Uganda found that blindness was caused by unoperated cataract in 13.1%, 9.1%, and 27.6% of children, respectively. 6 In Ethiopia, unoperated cataract or aphakia accounted for 9.2% of blindness in schools for the blind.…”
Section: Introductionmentioning
confidence: 73%